Effect of LiBF 4 salt concentration on the properties of poly(ethylene oxide)-based composite polymer electrolyte - Fahmi E.M.; Ahmad A.; Nazeri N.N.M.; Hamzah H.; Razali H.; Rahman M.Y.A. (2023)
Composite polymer electrolytes (CPEs) comprising a poly(ethylene oxide) (PEO) and nickel oxide (NiO) with different concentrations of lithium tetrafluoroborate (LiBF 4) are prepared using a solution casting technique. The structure and complexation of the electrolytes are studied by X-ray diffraction (XRD). The ionic conductivities of the electrolytes are measured at room temperature and shown that the addition of salt weight percent increased the ionic conductivity. The maximum conductivity (8.7510 -4 Scm -1) is obtained for a polymer complex with 30 wt. % LiBF 4. Scanning electron microscopy analysis showed that a rough surface of morphology of CPEs became smoother with addition of salt.